CEO compensation contagion: Evidence from an exogenous shock - Bereskin, Frederick L.; Cicero, David C. (Journal of Financial Economics, 2013)
We examine how Chief Executive Officer (CEO) compensation increased at a subset of firms in response to a governance shock that affected compensation levels at other firms in the economy. We first show that Delaware-incorporated firms with staggered boards and no outside blockholders increased CEO compensation following the mid-1990s Delaware legal cases that strengthened their ability to resist hostile takeovers. Consistent with the Gabaix and Landier (2008) contagion hypothesis, non-Delaware firms subsequently increased CEO compensation when the rulings affected a substantial number of firms in their industries. We further show how these legal developments contributed significantly to the rapid increase in CEO compensation in the late 1990s.